STRATEGI ORANG TUA ABANGAN DALAM MENGINTERNALISASIKAN NILAI-NILAI PAI PADA ANAK - Dwi Ramadhanti; Arditya Prayogi; Riki Nasrullah (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2025)
This research is motivated by the lack of optimal role of parents in providing role models or examples for children regarding worship. The lack of role models from parents makes the internalization of the values of Islamic religious education in children less than optimal. This article aims to describe the strategies of parents, especially those from abangan backgrounds, in internalizing the values of Islamic religious education in children in Bukur Village, Pekalongan Regency and what are the supporting and inhibiting factors. This article was prepared using a qualitative approach with a case study type supported by data collection techniques using interviews and observation. Data analysis techniques used are in the form of data reduction, data presentation, and drawing conclusions. From the results of the study, a description was obtained that there are three values of Islamic religious education taught to children, namely education of faith, morals and worship. In religious education, parents' strategy is to teach children the pillars of faith with the help of non-formal institutions such as madrasas in teaching it. In religious education, parents' strategy is to order and remind children to pray and recite the Koran, teach children to fast, and invite children to pay zakat. In moral education, parents will reprimand and advise children to always maintain good manners in behaving and speaking. The supporting factors in the abangan parents' strategy are the social environment and adequate facilities and the inhibiting factors are the parents' lack of understanding of religious knowledge, lack of parental attention, and the presence of laziness in children.